Encapsulation of Vitamin A Palmitate in Nanostructured Lipid Carrier (NLC)-Effect of Surfactant Concentration on the Formulation Properties - Akram Pezeshki; Babak Ghanbarzadeh; Maryam Mohammadi; Isa Fathollahi; Hamed Hamishehkar (Tabriz University of Medical Sciences, 2014)
Purpose: Nanostructured lipid carrier (NLC) is a useful delivery system with high capacity for bioactive loading, and suitable stability for fortification of foods and beverages. The objective of the present work is to prepare vitamin A palmitate (vitA)-loaded NLC and to investigate surfactant concentration effect on physicochemical properties of prepared formulation. Methods: VitA-loaded NLC was prepared by hot homogenization method. Preciol as solid lipid, Octyloctanoate as liquid oil, and Poloxamer as surfactant were used to prepare the formulation. The effect of different concentrations of Poloxamer on particle size, particle size distribution, encapsulation efficiency and stability of vitA during storage were investigated. Fourier transform infrared spectra (FTIR) was exploited to study the possible bioactive-lipid complex formation. Results: NLCs stabilized with 6% Poloxamer showed significantly lower particle size and particle size distribution. The encapsulation efficiency of this formulation was 98.5% and it was stable during the storage at 25°C for two months. Conclusion: This study suggests that surfactant significantly influences the final product properties. Our findings may pave the way of researchers to focus on fortifying the beverages with various lipophilic nutraceuticals.